The legalisation of cannabis: A security-vetting dilemma - Bester, Piet; Els, Sonja (Scientia Militaria - South African Journal of Military Studies, 2021)
During 1996, the South African Intelligence Community issued the Minimum Information Security Standards (MISS), which inter alia address the protection of classified information. The MISS provide the principles, standards and procedures to be followed by all South African government agencies for the protection of official resources.3 This includes the granting of different types and levels of security clearances by the South African government to provide employees and contractors access to classified information. The decision to grant a person access to classified information is based on such individual’s security competence. This is an indication of the person’s ability – based on his or her conduct – to prevent classified material from being disclosed to unauthorised persons, which may potentially prejudice or endanger the security or interests of the employing institution or the state. An applicant for a security clearance may be a prospective employee applying for a post from outside the organisation or an insider who is already in the organisation, often referred to as outsider and insider threats.4 The process of determining a person’s security competence is referred to as security vetting for new employees, and re-vetting for existing employees who have gone through the vetting process in the past.5 In this article, the use of the term ‘vetting’ includes re-vetting.